Urine Protein/Creatinine Ratios during Labor: A Prospective Observational Study - Tanamai, Vaya W. (PLoS One, 2016)
PURPOSE: To evaluate the utility of urine protein/creatinine ratio (uPCR) measurements among healthy parturients at term we performed a prospective cohort study at a community teaching hospital. METHODS: Serial urine samples were collected. Ninety-three women contributed 284 urine samples. uPCRs were determined. Multiple imputation and paired sampled analysis was performed when appropriate. RESULTS: Two-thirds (63/93) of women had at least one measured uPCR ≥ 0.3. One-third (31/93) had a uPCR ≥ 0.3 at admission, including 39.1% (9/23) of women not in labor. Median (IQR) uPCRs increased during labor and after delivery: latent phase/no labor, 0.15 (0.06–0.32); active phase, 0.29 (0.10–0.58); early postpartum, 0.45 (0.18–1.36) (all p < 0.04). Median uPCRs were significantly < 0.3 in the latent phase and significantly > 0.3 in the immediate postpartum period (p < 0.01). Women who labored before cesarean delivery had the highest early postpartum uPCRs: median (IQR) 1.16 (0.39–1.80). A negative urine dipstick protein result did not exclude uPCR ≥ 0.3. uPCRs were similar when compared by method of urine collection. CONCLUSION: uPCR ≥ 0.3 is common among healthy women with uncomplicated pregnancies at term. uPCR increases during labor and is not a reliable measure of pathologic proteinuria at term or during the peripartum period.